A new prototype of an electronic jet-ventilator and its humidification system - Kraincuk, Paul (BioMed Central, 1999)
BACKGROUND: Adequate humidification in long-term jet ventilation is a critical aspect in terms of clinical safety. AIM: To assess a prototype of an electronic jet-ventilator and its humidification system. METHODS: Forty patients with respiratory insufficiency were randomly allocated to one of four groups. The criterion for inclusion in this study was respiratory insufficiency exhibiting a Murray score above 2. The four groups of patients were ventilated with three different respirators and four different humidification systems. Patients in groups A and B received superimposed high-frequency jet ventilation (SHFJV) by an electronic jet-ventilator either with (group A) or without (group B) an additional humidification system. Patients in group C received high-frequency percussive ventilation (HFPV) by a pneumatic high-frequency respirator, using a hot water humidifier for warming and moistening the inspiration gas. Patients in group D received conventional mechanical ventilation using a standard intensive care unit respirator with a standard humidification system. SHFJV and HFPV were used for a period of 100 h (4days). RESULTS: A significantly low inspiration gas temperature was noted in patients in group B, initially (27.2 ± 2.5°C) and after 2 days (28.0 ± 1.6°C) (P < 0.05). The percentage of relative humidity of the inspiration gas in patients in group B was also initially significantly low (69.8 ± 4.1%; P < 0.05) but rose to an average of 98 ± 2.8% after 2 h. The average percentage across all four groups amounted to 98 ± 0.4% after 2 h. Inflammation of the tracheal mucosa was found in patients in group B and the mucosal injury score (MIS) was significantly higher than in all the other groups. Patients in groups A, C and D showed no severe evidence of airway damage, exhibiting adequate values of relative humidity and temperature of the inspired gas. CONCLUSION: The problems of humidification associated with jet ventilation can be fully prevented by using this new jet-ventilator. These data were sustained by nondeteriorating MIS values at the end of the 4-day study period in groups A, C and D.